Data Mining Untuk Melihat Minat Belajar Siswa Menerapkan Metode K-Means - Dudih Gustian; Muhamad Salman Al-Farits (Journal of Information System Research (JOSH), 2023)
Due to the lack of motivation to learn and learning method using the old method which is very boring, learning planning is currently a burden for educators and educthe ation of children at the junior high level. As a result, the purpose of this study aims at a learning system to create a learning plan for children using ICT. This educational institution known as Al-Furqon can be found in Kadudampit District, Sukabumi Regency. Outdated lecture methods are still used in teaching and learning activities in this school. Because it was previously used as a means of oral communication between teachers and students during the teaching and learning process, this method affects learning in MTs because it cannot be left behind in teaching activities even though it requires more teacher activities than students. Al-Furqon. There was no interesting interaction between students and teachers, and as a result, they became increasingly dissatisfied with traditional teaching approaches, K-Means algorithms and Data Mining techniques were used in the study. Clustering is also used. Data on Teaching Method Value, Learning Facility Value, Grade Condition Value, Environmental Influence Value, and Teacher Professionalism Value were used for testing in this study. to find out students' interests in school by grouping their data and applying K-Means Clustering analysis. It is hoped that after the number of students who are lacking or not interested in learning is identified, it will become the basis for this website design system to be a solution to the problem.